An Additional Adequate Water Intake Increases the Amniotic Fluid Index in Pregnant Women with Oligohydramnios: A Systematic Review - Rosemiarti, Tria; Siregar, Parlindungan; Hardinsyah, Hardinsyah; Pardede, Sudung O.; Santoso, Budi Iman; Riza, Ras Adiba; Tjahjono, Erinna (Jurnal Gizi dan Pangan, 2022)
This systematic review aimed to answer whether an additional amount of water intake can increase the Amniotic Fluid Index (AFI) in pregnant women with oligohydramnios. Article searches were conducted and data was obtained from “SCOPUS”, “EBSCO”, “PUBMED”, “COCHRANE” and “Google Search” databases using the following keywords: “hypovolemic”, “dehydration” “pregnancy” “outcome”, “hydration”. “water intake”, “oligohydramnios”, and “amniotic fluid index”. We used MeSH headings (hydration pregnancy) for search keyword, Inclusion criteria were subjects who were pregnant women with oligohydramnios (without any pathological disorder in the mother and fetus), the outcomes include AFI of <5 cm, study design was prospective cohorts and clinical trials, consumption of plain water (non-calorie beverages) and language restriction applied for articles published in English. Out of 391 articles, eight articles that met these criteria for anaylsis. Result showed that additional amount of water intake for pregnant women with oligohydramnios without maternal/fetal abnormalities in the third trimester (28−37 weeks) can increase AFI. Oral maternal hydration gave a better effect than intravenous maternal hydration on AFI. The additional amount of water intake per day required by pregnant women with oligohydramnios to increase AFI to normal ranges from 1,500 to 2,500 ml depending on the condition of each pregnant woman. Additional water intake via oral can be a strategy for oligohydramnios therapy in pregnant women.